Google sites-based network system administration learning media to enhance students critical thinking skills - Bulhadi Bulhadi; Refdinal Refdinal; Risfendra Risfendra; Muhammad Adri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to develop a Google Sites-based learning media for the Network System Administration subject to enhance the critical thinking skills of vocational high school (SMK) students. The research was motivated by the low level of student engagement in learning that remains predominantly teacher-centered, the limited utilization of digital learning resources, and the low achievement results that fall below the established Learning Achievement Criteria (KKTP). The research employed a Research and Development (R&D) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were eleventh-grade students of the Computer and Network Engineering program at SMK Negeri 6 Padang. The instruments used included validation questionnaires, practicality tests, and critical thinking tests. Data were analyzed through descriptive quantitative methods and the N-Gain formula to assess media effectiveness. The results showed that the Google Sites-based learning media obtained an average validity score of 92.5% (very valid), practicality score of 91.7% (very practical), and effectiveness with an N-Gain score of 0.65 (moderate to high category). The implementation of this media increased students’ engagement, encouraged productive use of digital devices, and improved critical thinking abilities in analyzing, evaluating, and solving problems.